Hubungan Pengetahuan dengan Sikap Ibu Nifas Tentang Pijat Oksitosin di Puskesmas Bergas - Susi Purwanti; Listiyaningsih, Moneca Diah (Universitas Ngudi Waluyo, 2021)
Referring to WHO program in 2025 targets exclusive breastfeeding of at least 50%. So nationally, the coverage of exclusive breastfeeding at the Bergas Health Center is 48%. The main reason for mothers not to exclusively breastfeed them is that in the first days after delivery the milk does not come out smoothly, so mothers prefer to give their babies formula milk. Oxytocin massage is an attempt to overcome the unsustainability of breast milk. The research objective was to determine the correlation between of knowledge and postpartum mothers' attitudes about oxytocin massage at the Bergas Health Center. Designof this research iscorrelation with the total population of postpartum mothers in October-November 2020 as many as 35 respondents, the study sample was 35 respondents with a total sampling technique. The instrumen used was a questionnaire with data analysis using the Chi Square test. The results of the univariate analysis of the knowledge variable showed that the respondents' knowledge was mostly good, namely 13 respondents (37.2%). And the attitude variable shows that 51.4% of respondents have negative attitudes. Bivariate analysis obtained sigifikansi value of 0,016 (Î± <0.05), so that H0 is rejected and Ha accepted. So it can be concluded that there is a relationship between knowledge and postpartum mothers 'attitudes about oxytocin massage at the Bergas Health Center in 2020. There is a relationship between knowledge and postpartum mothers' attitudes about oxytocin massage at the Bergas Health Center in 2020. ABSTRAKMengacu pada program WHO pada tahun 2025 sasaran pemberian ASI eksklusif minimal 50%. Maka secara nasional cakupan ASI Eksklusif di Puskesmas Bergas sebesar 48% belum terpenuhi. Alasan utama Ibu tidak memberikan ASI secara eksklusif adalah pada hari-hari pertama pasca melahirkan ASI keluar tidak lancar, sehingga ibu lebih memilih memberikan bayinya susu formula. Pijat Oksitosin adalah upaya mengatasi ketidaklancaran ASI. Tujuan penelitian adalah mengetahui hubungan pengetahuan dengan sikap ibu nifas tentang pijat oksitosin di Puskesmas Bergas. Desain penelitian ini korelasi dengan jumlah populasi Ibu nifas pada bulan Oktober-November 2020 sebanyak 35 responden, sampel penelitian berjumlah 35 responden dengan tekhnik pengambilan sampel total sampling. Instrumen yang digunakan adalah kuesioner dengan analisis data menggunakan uji Chi Square.Hasil analisis univariat variabel pengetahuan menunjukkan pengetahuan responden sebagian besar baik, yaitu sebesar 13 responden (37,2%). Dan variabel sikap menunjukkan sebanyak 51,4% responden memiliki sikap negatif. Analisis Bivariat didapatkan nilai sigifikansi sebesar 0,016 (Î±<0,05), sehingga H0 ditolak dan Ha diterima. Maka dapat disimpulkan bahwa ada hubungan pengetahuan dengan sikap ibu nifas tentang pijat oksitosin di Puskesmas Bergas Tahun 2020. Terdapat hubungan antara pengetahuan dengan sikap ibu nifas tentang pijat oksitosin di Puskesmas Bergas Tahun 2020.